(untitled) (Jurnal Biota, 2020)
Mangrove snail, Terebralia palustris Linnnaeus 1967, was also found on Pannikiang Island, Barru Regency, South Sulawesi. This study aims to describe the fluctuation of T. palustris density in a year of observation. This research was conducted for ten months from August 2018 to July 2019. There were two research stations. Each station has a large plot measuring 10m x 10m and in it, five small plots are measuring 1m x 1m. Measurements of environmental parameters such as temperature, salinity, and pH were carried out in situ. This snail meat as much as 100gr also analyzed proximate. The proximate analysis of the snail shows that crude protein content is 18.73% so that the snail is very suitable to be used as a source of protein. The highest density is in July 2019 and the lowest density is in August 2018.